Does ISO 14001 work in Brazil? - de Oliveira, Otavio Jose [UNESP]; Serra, Jose Roberto; Salgado, Manoel Henrique (Elsevier B.V., 2010)
As a result of increasing global awareness about the importance of the environment, depletion of natural resources and legal pressures for companies to manage their processes in a sustainable manner, ISO 14001 systems have been gaining increasingly more importance in the organizational scenario. These elements are even more critical in emerging nations due to less awareness and fewer demands by governments and the population in relation to environmental issues. Therefore, the main objective of this study is to verify the benefits and difficulties of Environmental Management Systems based on ISO 14001 at industries in the state of São Paulo - Brazil (an emerging country) by conducting a survey to subsidize the proposal for actions in the public, academic and private sectors to promote the use of this standard of reference and strengthen its results in Brazil. A questionnaire was sent to 194 companies from the National Institute of Metrology, Standardization and Industrial Quality database. 69 answered, representing a return rate of 35.36%. The main benefits identified are related to the development of preventive environmental actions, reduction in the consumption of power, water, gas and fuel oil, and a positive influence on other internal management processes. The main difficulties are related to cost increases from ISO 14001 management systems and the constant changes in environmental legislation in Brazil. Some actions are proposed at the end of the analyses to intensify the use and improve the results of this standard, such as changes in government legislation and its collective development and implementation in industries. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: ISO 14001; Environmental management; Environmental management systems; Developing countries; Brazil